Kerangka Kerja Untuk Menganalisis Praktik Akuntan Publik Sebagai Institusi Sosial - Rommel Togatorop; Rimi Gusliana Mais (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Accountant is regarded as one of the highly significant fields of discipline in contemporary societies. In recognizing its contributions to the larger society, this paper developed a framework to determine if public accountancy practice has become an institution, being a sector of society. In the sociological perspective, accounting can be aligned with other social institutions as it is perceived to make significant contributions to the long-term well-being of society. At the conceptual level, accounting still generates changes and debates among accounting experts and researchers. The emerging and prevailing accounting practices sometimes lead to diverse interpretations. The paper concludes that the state of condition, roles, and contributions of the public accountancy firms be documented through a scientific research that could be a source of knowledge and a basis for innovation in the profession and organizational growth of the individual auditing firms. Results can also be used in setting technical standards and regulatory pronouncements.